Efeitos da subfração CMS2, derivada do látex de Vasconcellea cundinamarcensis, sobre parâmetros de diferenciação em linhagem celular de melanoma murino B16F10 - Verlane Gonçalves Santos (2018)
CMS2 is a proteolytic subfraction from the latex of Vasconcellea cundinamarcensis, which shows antimetastatic activity on murine models of colon carcinoma and melanoma. Previous in vitro studies showed increased DNA fragmentation, decreased adhesion and cellular invasiveness of tumor cells exposed to the fraction. The aim of this study was to investigate cellular and molecular mechanisms involved in the antitumor and antimetastase activity of the CMS2 subfraction, using the B16F10 melanoma cell line. For this, the cytotoxic concentration of the subfraction, which corresponds to 10 μg/mL, was determined. Subsequently, B16F10 cells were exposed to CMS2 (1-10 μg/mL) for 2 to 8 days and then removed from the presence of the subfraction. First, the cell viability analysis showed a maximum reduction of 14% in cells previously exposed to CMS2. The melanogenesis may influence the behavior of melanoma cells, therefore melanin synthesis by cells exposed to subfraction has been evaluated. It was observed that CMS2 5 or 10 μg / mL promoted an increase in melanin content, which was higher in the 6-day period (73 and 96%, respectively) and was accompanied by the stimulation of tyrosinase activity. Thus, it was observed that the maximum effect of CMS2 on cell viability and melanogenesis occurred after 6 days of exposure and, mainly, at concentrations of 5 and 10 μg / mL, therefore, these parameters were used for the sequence of this study. In the next step, we observe a lower protein expression of the Transcription Factor associated with Microphthalmia (MITF) in the treated cells, in addition, the levels of mRNA expression for the enzymes Tyrosinase, TYRP-1 and -2 were not altered. Although MITF is associated with melanogenesis, a dual role is described for this factor, which at high levels favors cell proliferation and survival, which may justify its lower expression. When assessing the influence of CMS2 on the morphology of B1610, we observed that subfraction induced the formation of cellular dendrites, which agrees with the stimulation of melanogenesis in these cells. The melanogenesis may inhibit cell proliferation, therefore, cell cycle analysis was performed. We observed the induction of cell cycle arrest in the G1 phase by CMS2, without inducing increase in the content of subdiploid DNA. However, no differences in β-galactosidase activity and p53 expression were observed, while p21 expression was reduced by 92% in the treated cells, showing that the cells are not senescent. When investigating events of the tumor development, it was verified that CMS2 reduced the migration and cellular invasion, besides inhibiting the formation of colonies in vitro. These effects are related to less activation of the signaling pathways of MAPKs (ERK1 / 2 and p38) and AKT. In addition, subfraction inhibited the expression of the N-cadherin adhesion molecule. Finally, in the in vivo model, the cells exposed to CMS2 presented lower capacity of lung colonization in relation to the control cells. In conclusion, we observed that CMS2 interferes in tumor development, inducing a less aggressive phenotype in B16F10 cells. This may explain the antimetastase activity already described for subfraction and contribute to justify its potential use in the treatment of cancer.